2019
DOI: 10.1101/838581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term warming effects on the microbiome and nitrogen fixation of a common moss species in sub-Arctic tundra

Abstract: Bacterial communities form the basis of biogeochemical processes and determine plant growth and health. Mosses, an abundant plant group in many Arctic ecosystems, harbour diverse bacterial communities that are for instance involved in nitrogen fixation. Global climate change is causing changes in aboveground plant biomass and shifting species composition in the Arctic, but little is known about the response of the moss microbiome. Here, we study the bacterial community associated with the moss Racomitrium lanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 129 publications
(199 reference statements)
1
2
0
Order By: Relevance
“…The C. islandica-associated microbiota was found to be markedly different to that of the moss Racomitrium lanuginosum which was studied in the same warming experiment (Klarenberg et al, 2019), further supporting the host-specific selection of bacteria from the environment and symbiotic nature of both bryophyte and lichen holobionts proposed in the recent literature (Aschenbrenner et al, 2016;Holland-Moritz et al, 2018). Specifically, we found that C. islandica harbored a less rich and diverse bacterial community than R. lanuginosum, and the microbiota composition was profoundly different.…”
Section: The Bacterial Community Of Cetraria Islandicasupporting
confidence: 82%
See 1 more Smart Citation
“…The C. islandica-associated microbiota was found to be markedly different to that of the moss Racomitrium lanuginosum which was studied in the same warming experiment (Klarenberg et al, 2019), further supporting the host-specific selection of bacteria from the environment and symbiotic nature of both bryophyte and lichen holobionts proposed in the recent literature (Aschenbrenner et al, 2016;Holland-Moritz et al, 2018). Specifically, we found that C. islandica harbored a less rich and diverse bacterial community than R. lanuginosum, and the microbiota composition was profoundly different.…”
Section: The Bacterial Community Of Cetraria Islandicasupporting
confidence: 82%
“…In contrast, the decreased relative abundance and potential activity of Bryocella and Acidiphilium might result in slower degradation of dead lichen material. The genus Acidiphilium showed an increase in relative abundance in a moss microbiome in the same warming experiment (Klarenberg et al, 2019). This suggests that the responses of microbiome components to environmental change are at least in part dependent upon host vegetation identity rather than constituting a direct response of the bacteria themselves to extrinsic environmental factors.…”
Section: The Bacterial Community Of Cetraria Islandicamentioning
confidence: 89%
“…Moss microbes contribute around 50% of N inputs to boreal forests, play crucial roles in facilitating C degradation in peatlands, and facilitate host adaptation in degraded landscapes [6]. Moss-associated microbial communities are notably dominated by bacteria from the Proteobacteria, Acidobacteria, Actinobacteria, and Cyanobacteria phyla [7][8][9]. Driven by the pressures of accelerating climate change, boreal ecosystems face a temperature increase of ~2.5ºC before the end of the century, which could alter moss-microbe interactions with major implications for global N [10] and C cycles [11].…”
Section: Introductionmentioning
confidence: 99%